Preparation of 5-(p-Chlorophenylazo) Resacetophenone by Two Routes and Using its Oxime as Reagent for Qualitative and Quantitative Analysis of Some Bivalent Metals - Bhattacharya, Ira (Asian Journal of Chemistry, 2010)
Resacetophenone was synthesised from resorcinol by Nencki's reaction and then coupled with diazonium salt of p-chloroaniline-to'obtain 5-(p-chlorophenylazo) resacetophenone. An alternate route was tried by changing the sequence of the reaction. Resorcinol was first coupled with diazonium salt of p-chloroaniline and then subjected to Nencki's reaction. The results of experiments, elemental analysis and IR spectral data suggested that the compounds obtained by both the methods were same. These also indicated that coupling before or after Nencki's reaction did not involve any structural change. Position of coupling was ascertained by the preparation of reductive derivative of the azo compound followed by conversion of —NH2 group to —OH group. Further, the compound was converted to its oxime with hydroxylamine hydrochloride. The oxime was coloured and had high molecular weight. It was consequently used as a chelating agent for qualitative and quantitative analysis of bivalent metals like Cu, Zn and Ni. On the basis of the quantitative data the structures of the complexes were assigned and probable use of the oxime as analytical reagent was suggested.